A new species of Bathylepeta Moskalev, 1977 (Mollusca: Gastropoda) from the Weddell Sea, Antarctica - Schwabe, Enrico (Zootaxa, 2006)
Among benthic mollusc samples from the abyssal of the Weddell Sea collected during the ANDEEP III Antarctic survey, a new lepetid species Bathylepeta linseae n. sp. was collected and is here described. The new species strongly resembles the only congener Bathylepeta laevis Moskalev, 1977 but differs in a more oval shell shape, the rectangular form of the radular basal plate and the smooth edges of the marginal teeth. The presence of a genital papilla is mentioned for the first time for this genus. Another similar Antarctic lepetid species Propilidium pelseneeri Thiele, 1912 is much smaller, lacks the genital papilla and the position of the apex is more posteriorly.